Pancreatic acinar cells: membrane potential and resistance change evoked by acetylcholine - Nishiyama, A. (1974)
1. Membrane potential and input resistance measurements were made on segments of pancreas from mice or rats, whereas potential measurements alone were made on pancreas from cats or rabbits placed in a tissue bath which was perfused with a Krebs—Henseleit solution. 2. The acinar cell membrane potential was about -40 mV and the input resistance 4-8 MΩ. Spontaneous miniature depolarization potentials were occasionally observed superimposed upon the resting potential. In these cases synchronous reductions in input resistance were observed. 3. The immediate effect of stimulation with ACh was always a depolarization and a concomitant reduction in input resistance and time constant. In some cases a secondary depolarization was observed accompanied by an increase in input resistance. The time constant, however, remained as short as in the first phase of depolarization. 4. In the rabbit pancreas ACh evoked biphasic potential changes: depolarization followed by hyperpolarization. A similar pattern could sometimes also be observed in the mouse pancreas following a brief pulse of ACh addition. In these cases the depolarization was followed by a small but relatively long lasting hyperpolarization. The depolarization was accompanied by a reduction in input resistance. 5. Pancreozymin caused depolarization of the acinar cell membrane and a marked reduction in input resistance and time constant. 6. In the presence of atropine (1·4 × 10(-6) M) depolarization of the acinar cell membrane by an elevated K concentration (50 mM) in the bathing fluid did not reduce the input resistance. 7. It is concluded that the two physiological stimulants of pancreatic protein secretion, ACh and pancreozymin, act on the acinar cells by increasing the permeability of the plasma membrane.